Focused group discussion with health care staff improves breastfeeding rates in hospitalized infants - Agnes Yunie Purwita Sari; Rosalina Dewi Roeslani; Rinawati Rohsiswatmo (Paediatrica Indonesiana, 2017)
Background Improving breastfeeding in sick infants is essential. During the neonatal care, health care staff play an important role in promoting breastfeeding. Therefore, it is important to study in depth how healthcare staff can improve breastfeeding practice in sick neonates.Objective To compare breastfeeding rates in sick infants before and after a focused group discussion (FGD) of health care staff on how to improve breastfeeding.Methods This study was an operational study using FGD and in-depth interviews as an intervention. A fish bone diagram was used to assess problems that may prevent mothers from breastfeeding their sick infants. Breastfeeding achievement was compared before and after the FGD.Results Of 257 sick infants, 177 subjects were in the before FGD group and 80 subjects were in the after FGD group. Significantly more after FGD subjects were breastfed during hospitalization than before FGD subjects [97.5% vs. 82.9%, respectively; (x2 =9.43; P=0.002)]. Breastfeeding initiation within 0-4 hours of birth was also significantly higher in the after FGD group [10 (12.5%) vs. 6 (3.5%), respectively; (x2 = 52.5; P<0.001)]. The solutions for breastfeeding problems were: 1) support of hospital management, 2) support of healthcare workers for breastfeeding mothers, 3) support of husbands and families for breastfeeding mothers, 4) financial support, 5) other factors such as level of care and consistent FGD events, and 6) a prospective cohort study.Conclusion The FGD with health care staff significantly increases breastfeeding achievement during infant hospitalization, and accelerated breastfeeding initiation. A fish bone diagram is used to effectively assess the problems with breastfeeding programs for sick babies.